Primary Bone Marrow Lymphoma with Secondary Central Nervous System Involvement: a case report - Hari Priya Raghyan,; Alia Suzana Asri,; Hafiza Alauddin,; Reena Rahayu Md Zin,; Nor Rafeah Tumian,; Sivakumar Palaniappan,; Raja Zahratul Azma Raja Sabudin, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
Primary bone marrow lymphoma (PBML) is a rare condition. Most PBMLs are B-cell non-Hodgkin lymphomas (NHLs), where predominated by the diffuse large B-cell lymphomas (DLBCLs). Non-Hodgkin lymphomas affects extranodal sites in one-third of cases. Secondary central nervous system lymphoma (SCNSL) is a rare state which is defined as secondary central nervous system (CNS) involvement in patients with systemic lymphoma. In this report, we described a case of primary bone marrow lymphoma with secondary involvement of the CNS. Patient presented with neurological deficit. Peripheral blood film showed presence of abnormal mononuclear cells. Histopathological examination of the brain tissue showed features of DLBCL with CD10 positivity. Bone marrow examination showed presence of lymphoma cells. He was commenced with Rituximab, methotrexate, vincristine and procarbazine (R-MPV). However, he succumbed after two cycles of chemotherapy.